The Role of Higher Education in Managing Conflict Situations in Society for Sustainable Development: A Case Study Of UMP’s Contribution in the Controversial Lynas Rare Earth Project - Badhrulhisham, Abdul Aziz (2016)
Between 2010 - 2013, a project involving production of rare earth metals (for green and high technology application) in Kuantan, Pahang attracted worldwide attention due to the concerns on the effects of radioactive to the safety and health of the community, and environment. In addition to the safety, health and environmental issues, several important issues were also raised such as investment policies, and community engagement. This paper will highlight the roles and contributions of Universiti Malaysia Pahang (UMP), a technical university located near the production area, in dealing with the issues. UMP played a major role, not only in providing technical support to the government through it’s involvement in several related agencies and committees, but also in engaging the community in raising awareness of the issues. The involvement was not a one-off type but a continuous one with the set up of a monitoring center and a research center to support the sustainable development of the industry. This is very significant in the efforts of making universities relevant to various stakeholders and in gaining trust and respect of the community.